The Influence of Various Growth Regulators on Induction Organogenic Callus from Gajah and Kuning Cassava Genotype (Manihot esculenta Crantz) - Rahman, Nurhamidar; Fitriani, Hani; Rahman, Nurhaidar; Hartati, N. Sri (Jurnal ILMU DASAR, 2021)
Kuning and Gajah genotypes are two collections of cassava in the Biotechnology Research Center for Germplasm, LIPI with the advantages of each genotype are high beta carotene and high production. The multiplication in in vitro culture can be done one of them through organogenesis. The aim of this study was to evaluate the effect of using 2,4-D; NAA and Kinetin are used singly for the formation of organogenesis of cassava in the Kuning Cassava and Gajah genotypes. This research was conducted at the Laboratory of Molecular Genetics and Modification of Plant Biosynthetic Pathways, Biteknologi Research Center, LIPI, Bogor since January - February 2018. The source of explants were young leaves and petiols from cassava plant culture in vitro genotypes of Gajah and Kuning yam which were three months old. in culture. The basic media used as a planting medium were Murashige and Skoog (MS) media with the addition of growth regulators (ZPT) singly, 2,4-D, NAA and Kinetin with two concentrations of ZPT each, 8 and 10 mg L- 1 This research was arranged based on a completely randomized design factorial pattern consisting of 2 factors. All data obtained were analyzed using ANOVA and if there is an influence then proceed with the DMRT test with an error rate of 5% using the SPSS program. The highest number of Kuning genotype cassava organogenic callus that developed into shoots on the medium added by ZPT was 2.4 D and kinetin with the same concentration of 8 mg L-1. Formation of the best organogenic callus in petiol explants in the media with the addition of a single 2,4-D and Kinetin with the same concentration of 8 mg L-1. Keywords: Cassava, growth regulators, organogenic.